2013
DOI: 10.1371/journal.pone.0072967
|View full text |Cite
|
Sign up to set email alerts
|

BET Inhibition Silences Expression of MYCN and BCL2 and Induces Cytotoxicity in Neuroblastoma Tumor Models

Abstract: BET family proteins are epigenetic regulators known to control expression of genes involved in cell growth and oncogenesis. Selective inhibitors of BET proteins exhibit potent anti-proliferative activity in a number of hematologic cancer models, in part through suppression of the MYC oncogene and downstream Myc-driven pathways. However, little is currently known about the activity of BET inhibitors in solid tumor models, and whether down-regulation of MYC family genes contributes to sensitivity. Here we provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 45 publications
8
143
0
Order By: Relevance
“…We found that, on JQ1 treatment, there was selective downregulation of the predominant MYC isoform in JQ1-sensitive DFs, consistent with the well-established role of BRD4 in promoting MYCN and c-MYC transcription (21)(22)(23)35). Consistently, selectivity of gene down-regulation following BRD4 inhibition has been ascribed to the presence of superenhancer regions, occupied by BRD4, and associated with the transcriptional regulation of key lineage-specific oncogenes and survival genes (36).…”
Section: Discussionsupporting
confidence: 83%
“…We found that, on JQ1 treatment, there was selective downregulation of the predominant MYC isoform in JQ1-sensitive DFs, consistent with the well-established role of BRD4 in promoting MYCN and c-MYC transcription (21)(22)(23)35). Consistently, selectivity of gene down-regulation following BRD4 inhibition has been ascribed to the presence of superenhancer regions, occupied by BRD4, and associated with the transcriptional regulation of key lineage-specific oncogenes and survival genes (36).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies of MYCN-amplified neuroblastoma have focused on the role of MYCN in transcriptional activation and the superenhancer machinery to drive a neuroblastoma oncogenic program (20,43,56,57). The role of MYCN in repressing tumor suppressor programs in neuroblastoma has not been as well explored.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that JQ1 suppresses growth of neuroblastoma in a set of in vivo models, including orthotopic transplantation of patient-derived xenografts and the TH-MYC mouse model (19,31). To determine the therapeutic effects of the TP-scaffold inhibitors in aggressive neuroblastoma, we established an s.c. xenograft model of MYCN-amplified neuroblastoma in immunocompromised mice using the SKNBE2 cell line.…”
Section: Intermolecular Contacts Of the Thienopyranone Substituents Pmentioning
confidence: 99%